1995
DOI: 10.1093/oxfordjournals.eurheartj.a060890
|View full text |Cite
|
Sign up to set email alerts
|

Above-normal left ventricular systolic performance during exercise in young subjects with mild hypertension

Abstract: Debate continues on whether left ventricular (LV) systolic function during exercise is abnormal in young subjects with mild hypertension and on whether the abnormal blood pressure (BP) trend observed in hypertensives during prolonged exercise is due to impaired LV function. LV function was measured by means of M-mode echocardiography during prolonged exercise in 13 physically trained, young, mild hypertensives and 12 age-matched, trained normotensives with similar working capacity. Systolic BP/end-systolic vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…This is confirmed by findings in other studies which reported an enhanced systolic function for patients after surgery with a moderate resting systolic blood pressure difference between the right arm and leg (Borow et al 1985;Moskowitz et al 1990;Tantengco et al 1997). An increased (above normal) left ventricular systolic performance during exercise has been reported in young subjects with mild hypertension (Palatini et al 1995). Overcompensation of a slight increase in aortic resistance can contribute to a slight cardiac hypertrophy, as seen in athletes (Sharma et al 2002), increasing stroke volume and muscle perfusion.…”
Section: Discussionmentioning
confidence: 96%
“…This is confirmed by findings in other studies which reported an enhanced systolic function for patients after surgery with a moderate resting systolic blood pressure difference between the right arm and leg (Borow et al 1985;Moskowitz et al 1990;Tantengco et al 1997). An increased (above normal) left ventricular systolic performance during exercise has been reported in young subjects with mild hypertension (Palatini et al 1995). Overcompensation of a slight increase in aortic resistance can contribute to a slight cardiac hypertrophy, as seen in athletes (Sharma et al 2002), increasing stroke volume and muscle perfusion.…”
Section: Discussionmentioning
confidence: 96%
“…A preliminary cycle ergometer test to exhaustion in a 30% gradient semi-supine position served to evaluate _ V O 2max and anaerobic threshold (Wasserman and McIlroy 1964) using the procedure reported elsewhere (Palatini et al 1995). Expired gas was continuously analysed for percentage of oxygen and carbon dioxide using a Datex O 2 -CO 2 fast response analyser.…”
Section: Methodsmentioning
confidence: 99%
“…During the ®rst 10 min of exercise, the intensity was progressively increased to attain the level previously reached at the anaerobic threshold, then the subjects continued pedalling to exhaustion. M-mode echocardiograms were performed using a SPR 8000 (Hitachi, mod EUP 121, Tokyo, Japan) under two-dimensional guidance (Palatini et al 1995). LV images were obtained at end-expiration.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations